A formação do sujeito moral na perspectiva kantiana - Martins, João Paulo Silva (2016)
The philosopher Immanuel Kant conceives man as a rational human being, capable to develop and improve yourself. Other animals found in the instinct their way of being and how to proceed, but the man, being endowed with reason, must be formed by yourself. Thus, the objective of this study was to analyze the moral formation process of man under the Kantian perspective, considering its proposals and methods aimed at the development of humanity, both in relation to the individual, and in relation to the species. For realization of this objective will be taken as the primary reference text About Education, in which education is presented as a means to remove the man from his state of animal bluntness and lead it to the maximum improvement of his rational nature: morality as an individual; cosmopolitanism as a species.